A super-resolution CMOS image sensor for bio-microfluidic imaging - Wang, Tongxi (2013)
A super-resolution CMOS image sensor is introduced in this paper for bio-microfluidic imaging. Compared to the traditional scientific CCD or CMOS image sensor, our design achieves the balance between high-sensitivity and high-resolution from system design perspective with the use of single-frame super-resolution. Moreover, the column-parallel image sensor architecture with correlated-double-sampling is deployed for high-speed and low-noise readout. The chip is designed in standard 0.18μm CMOS mixed-signal process with area of 2.5mm×5.0mm, 128×128 pixel-array and speed of 1750 frames/s. The resolution is improved by 4X by on-chip super-resolution algorithm while large pixel (10μm×10μm) is employed in image sensor for high-sensitivity.